Diffusion of methyl oleate in hierarchical micro-/mesoporous TS-1-based catalysts probed by PFG NMR spectroscopy. Issue 68 (20th November 2018) - Dvoyashkin, Muslim; Wilde, Nicole; Haase, Jürgen; Gläser, Roger
Abstract : Direct assessment of methyl oleate diffusion confined to nanopores of TS-1-based catalysts by means of pulsed field gradient NMR. Abstract : Pulsed field gradient (PFG) NMR is successfully applied to trace the diffusion of methyl oleate (MO) inside the mesopores of hierarchically structured titanium silicalite-1 (TS-1)-based catalysts. Introduction of mesoporosity by post-synthetic treatment of initially microporous TS-1 provides additional active surface to improve catalytic activity in the epoxidation of MO. The present study provides experimental evidence of the accessibility of mesopores for MO resulting from alkaline treatment of TS-1. The self-diffusion coefficients of MO inside the pores of hierarchically structured TS-1 catalysts are up to two orders of magnitude lower compared to the values in the bulk liquid phase. Additionally, the methodological capability of PFG NMR for measuring self-diffusion coefficients of long-chain hydrocarbons (up to C19) confined to narrow mesopores of catalytically active is demonstrated for the first time.